Nilai Religius dalam Legenda Masjid Sunan Muria dari Kumpulan Cerita Rakyat Pesisir Timur - Vika Irmainsyah; Muhammad Afdholil Kholiqoh Insani; Adam Sidqi; Mohammad Kanzunnudin (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to uncover and analyze the religious values ​​contained in the story of the Legend of the Sunan Muria Mosque by Mohammad Kanzunnudin, which is included in the book Cerita Rakyat Pesisir Timur. The study used a descriptive qualitative approach with a listening-noting technique to identify religious elements in the text. The results of the study indicate that the religious values ​​in this story include three main dimensions as stated in Permendikbud Number 20 of 2018. First, the dimension of the relationship between humans and God is depicted in Sunan Muria's determination to establish a mosque as a form of worship, spiritual perseverance, tawakal, and patience in the face of failure. Second, the dimension of the relationship with fellow humans is seen in the cooperation between Sunan Muria and Sunan Kudus in spreading Islam, as well as social interactions that reflect the spirit of brotherhood. Third, the dimension of the relationship with nature is reflected in the selection of a mosque location that is in harmony with the environment and the use of natural materials such as river stones, teak wood, and reeds, without damaging the surrounding environment. This story proves that folk legends not only contain historical elements, but also store spiritual values ​​that can be used as a medium for learning religious character for children.